The Effect of 12 Weeks of Using Stability Ball in Working Environment on the Intensity of Pain and Disability in the People with Chronic Low Back Pain - Jafar Ketabchi (Journal of Global Pharma Technology, 2017)
Introduction: low back pain is common among the employees who sit at the table for long hours. Comparing to sitting on office chair, sitting on stability balls causes activation of the core muscles of the body. Increasing the activity of core muscles in the central part of the body causes the increase of stability in Lumbo-pelvic-Hip complex which can be efficient in improving the pain, signs and symptoms of the patients with chronic low back pain. The objective of the present study was the transitional use of 12 weeks of stability ball instead of office chairs on pain indexes and disability in the patients with chronic low back pain. Material and methods: 28 men suffering from chronic low back pain (mean± standard deviation of age 4/2±5/39،BMI, 9/1±2/24) were selected to take part in the study through convenient method. The participants of the present study used stability ball for 12 weeks instead of office chair during some hours of their working (maximum two hours) at the office. The pain intensity and disability of the subjects were measured through applying QUEBEC and OSWERTRY questionnaires. Dependent sample t-test was used at 0.05 levels to analyze the data. Findings: a significant difference was observed in the relationship between pain intensity and disability in the participant people (P<0.05). The mean of pain intensity and disability in the people participating in the pretest were 26.4±5.0 and 24.2±5.4 respectively. After administering therapeutic protocol, the mean of pain intensity and disability decreased to 18.6±4.7 and 21.2±4.7 which showed an improvement of 29% and 12% in the pain intensity and disability in these patients. Conclusion: sitting on stability ball leads to more activation of core muscles of the body especially deep stabilizers in this part. Activating deep stabilizers in the core part leads to the improvement of the condition of patients suffering from chronic low back pain. According to the results of the current study, sitting on stability ball instead of office chair in working hours can cause more activation of core muscles. Therefore it is recommended to use stability balls instead of office chairs. although just the improvement of working environment cannot lead to the treatment and improvement, so making such changes along with other therapy modalities can cause more effectiveness on the condition of the patients suffering from chronic low back pain.Keywords: Chronic low back pain, Stability ball, Quebec questionnaire, Core stability, Oswertry questionnaire.